Direito autoral e preservação digital: Considerações pertinentes a periódicos científicos eletrônicos mantidos no sistema LOCKSS - Dias, Guilherme Ataíde [UNESP]; de Sousa, Rosilene Paiva Marinho; Rodrigues Paiva, Maria José (My University, 2012)
This paper discusses electronic journals preservation issue in the system Lots of Copies Keep Stuff Safre (LOCKSS), under the Brazilian author's rights legislation. It analyses whether the assignment of property rights of authors in scientific journals allow content replication into the system, so that their work becomes digitally preserved. This research is characterized as being exploratory and bibliographic. The research universe is constituted by electronic journals from institutions that make use of the LOCKSS system through the Brazilian Network of Digital Preservation Services (Cariniana).
Intellectual property and digital preservation: Considerations relevant to electronic journals kept in the LOCKSS system
Keywords: Author's rights; Digital preservation; Electronic journals; Intellectual property; Lockss